Taḥlil As’ilah al-Tamrînât fî Kitâb al-Balâghah al-Muṣawwarah fî Far'i Ilm al-Bayân 'ala Ḍaw'i Taṣnîf Bloom fî al-Majâl al-Ma'ruf - Riska Wahyu Pratiwi Adnin Putri; Syihabuddin Syihabuddin (Alfaz (Arabic Literatures for Academic Zealots), 2021)
This research is the one that examined the analysis of exercise questions in the Book “al-Balaghah al-Musawwarah”, prepared by Ihab Abdel-Rasheed in the science of statement in the light of Bloom's classification of cognitive domain. The objectives of this research are to determine what are the levels measured by the exercise questions in the Book “al-Balaghah al-Musawwarah” prepared by Ihab Abdel-Rasheed, and to identify the percentage of these levels achieved by each level. The researcher analyzed the exercise questions in the Book “al-Balaghah al-Musawwarah”, prepared by Ihab Abdel Rashid in the science of rhetoric in the light of a special form that included the six levels of Bloom's classification (remembering, understanding, application, analysis, synthesis, and evaluation). The study found that the exercise questions in the Book “al-Balaghah al-Musawwarah” amounted to 113 questions. It measures the level of remembering 44.25%, at the level of understanding 32.74%, at the level of application 13.27%, and at the level of analysis 9.73%. The questions were completely neglected at the level of installation and evaluation.